2022
DOI: 10.52845/jmrhs/2022-5-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Pyonephrose:Riskfactors,clinical,para-clinicalandanatomopathologicalprofileabout19cases

Abstract: Introduction:Ponephrosis is a severe infection which is defined by the destruction of the renal parenchyma by a suppurative process within the dilated pyelocaliceal cavities. Suspected clinically but his diagnosis is mainly based on imagery. Despite clinical and radiological knowledge, it remains a surprise for the surgeon. The objective of this work is to describe the risk factors, the clinical, paraclinical and histological profile of it. Patients And Methods:We report a retrospective uni-centric study condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The clinical presentation is variable, occasionally it can cause a mass with tumor characteristics, which requires a differential diagnosis with different pathologies such as clear cell carcinoma, sarcomatoid renal cell carcinoma, renal tuberculosis, renal lymphoma, renal or psoas abscess, actinomycosis, cystic disease kidney disease and emphysematous pyelonephritis [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical presentation is variable, occasionally it can cause a mass with tumor characteristics, which requires a differential diagnosis with different pathologies such as clear cell carcinoma, sarcomatoid renal cell carcinoma, renal tuberculosis, renal lymphoma, renal or psoas abscess, actinomycosis, cystic disease kidney disease and emphysematous pyelonephritis [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation is nonspecific and variable. Consider clear cell carcinoma, sarcomatoid renal cell carcinoma, renal tuberculosis, renal lymphoma, renal or psoas abscess, actinomycosis, renal cystic disease, and emphysematous pyelonephritis [2,3]. We present the case of a 59-year-old female patient, with a history of recurrent urinary tract infections, who came to our center due to severe anemia (5gr/dl), weight loss of 10 kg in 2 months, night sweats and weakness, concomitant sudden-onset lumbar pain and hematuria, after multiple studies, a diagnosis of PNX was made, which was confirmed by anatomopathological study.…”
mentioning
confidence: 99%